Peningkatan Keterampilan Jurnalistik Masyarakat Pelaku Industri Pariwisata Di Kecamatan Sukamakmur, Kabupaten Bogor - Rinie Octaviany Hasan; Mentari Anugrah Imsa; Rahmat Darmawan; Najla Hanna Qonita; Shakira Yasmin Az zahra (Pusat Riset dan Inovasi Nasional, 2023)
This activity aims to increase understanding and journalistic skills as an effort to optimize the tourism information system (SIPARIS) website by Sukamakmur District, Bogor Regency. It's because the role of the SIPARIS website is very important to inform about tourism potential in Sukamakmur District, but turns out that the SIPARIS website content is no longer updated and less informative. To make the website more attractive, the content must be made as informative as possible, so that users who want to know about tourism in Sukamakmur District can get complete information on the SIPARIS website. The participants of this training are website managers, tourism awareness groups, and tourism actors in Sukamakmur Sub-district who are expected to become resources for developing content and information on the website. The method used is a workshop to convey journalistic material, then practice the material that has been learned. The achievement of the success of this service is through pre-test and post-test after the workshop is completed. The result of the activity is the increase in knowledge as well as journalistic skills of the participants, to support the optimization of the SIPARIS website.